2015
DOI: 10.1530/joe-15-0391
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin modulates hypothalamic fatty acid-sensing and control of food intake in rainbow trout

Abstract: There is no information available on fish as far as the possible effects of ghrelin on hypothalamic fatty acid metabolism and the response of fatty acid-sensing systems, which are involved in the control of food intake. Therefore, we assessed in rainbow trout the response of food intake, hypothalamic fatty acid-sensing mechanisms and expression of neuropeptides involved in the control of food intake to the central treatment of ghrelin in the presence or absence of a long-chain fatty acid such as oleate. We obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 65 publications
6
41
0
Order By: Relevance
“…These changes support the activation of fatty acid-sensing systems by GHRL treatment, and most of them are in agreement with a previous study carried out in the same species under similar experimental conditions (Velasco et al, 2016a). The activation of these systems is also in agreement with the increased orexigenic potential observed simultaneously, as supported by decreased mRNA abundance of POMC and CART and increased mRNA abundance of NPY and AgRP, in a way comparable to that reported in mammals (Ramírez et al, 2013).…”
Section: Discussion Ghrl Treatment Does Not Affect Ceramide Levels Insupporting
confidence: 92%
See 4 more Smart Citations
“…These changes support the activation of fatty acid-sensing systems by GHRL treatment, and most of them are in agreement with a previous study carried out in the same species under similar experimental conditions (Velasco et al, 2016a). The activation of these systems is also in agreement with the increased orexigenic potential observed simultaneously, as supported by decreased mRNA abundance of POMC and CART and increased mRNA abundance of NPY and AgRP, in a way comparable to that reported in mammals (Ramírez et al, 2013).…”
Section: Discussion Ghrl Treatment Does Not Affect Ceramide Levels Insupporting
confidence: 92%
“…Moreover, GHRL is also involved in the control of glucose and lipid metabolism in fish (Kaiya et al, 2009;Salmerón et al, 2015). In a previous study in rainbow trout, we demonstrated that intracerebroventricular (ICV) GHRL treatment counteracts the effects in hypothalamus of raised levels of a LCFA-like oleate on the activity of fatty acid-sensing systems, the expression of neuropeptides and food intake (Velasco et al, 2016a).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations